A reliable method for the assessment of occupants' exposure to CO2. (15th October 2020) - Kierat, Wojciech; Melikov, Arsen; Popiolek, Zbigniew
Highlights: A new method for an accurate determination of the CO2 exposure was presented. Gas sampling synchronised with the inhalation phase of the breathing was tested. Independence of the measured CO2 concentration from the breathing mode was obtained. Abstract: Maximum CO2 exposure requirements for building occupants are defined in present indoor climate standards. In occupied spaces CO2 is generated mainly by air exhaled by the occupants and part of the exhaled air with high CO2 concentration is re-inhaled before it is mixed with the surrounding air. Therefore the CO2 concentration measured in any location in the room (including in the exhaust air) is different from the CO2 concentration in the inhaled air. This paper presents an apparatus for measuring exposure to CO2 . The apparatus is installed on a headset and equipped with a sampling tube located close to the mouth/nose and two pneumatic solenoid valves, and is controlled such that gas samples are taken only during inspiration. Gas sampling is synchronized with the inspiration period of the breathing cycle. The proposed system allows one to determine CO2 exposure more accurately than with the methods currently in use.